The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.energyfuels.9b00368
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of the Morphology and Nanostructure of Soot Particles for Butanol/Diesel Blends at Different Engine Operating Modes

Abstract: In order to comply with strict emission standards, a reduction in diesel particle matter emissions can be addressed by minimizing particle formation and by optimizing particle oxidation in the combustion chamber and in the exhaust and diesel particulate filter systems. The characterization of soot morphology and nanostructure is necessary to understand the soot formation and oxidation processes. Furthermore, understanding these characteristics is important because they affect the aerodynamic behavior of diesel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 106 publications
2
6
0
Order By: Relevance
“…n-Hexanol addition decreased the aromatic component, while it increased the oxygen content in the blends, which could inhibit particle surface growth but enhances soot oxidation, leading to small primary particles in size. Similar results have been reported in previous studies. ,, Li et al investigated the soot morphology in a laminar diffusion flame fueled with n -heptane, n-butanol, and H50B50 (50% n -heptane and 50% n-butanol, v/v), respectively. Their results showed that as the n-butanol content in blended fuels increased, smaller aggregates and primary particles were produced.…”
Section: Results and Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…n-Hexanol addition decreased the aromatic component, while it increased the oxygen content in the blends, which could inhibit particle surface growth but enhances soot oxidation, leading to small primary particles in size. Similar results have been reported in previous studies. ,, Li et al investigated the soot morphology in a laminar diffusion flame fueled with n -heptane, n-butanol, and H50B50 (50% n -heptane and 50% n-butanol, v/v), respectively. Their results showed that as the n-butanol content in blended fuels increased, smaller aggregates and primary particles were produced.…”
Section: Results and Discussionsupporting
confidence: 86%
“…Similar results have been reported in previous studies. 29,30,71 Li et al 71 investigated the soot morphology in a laminar diffusion flame fueled with n-heptane, n-butanol, and H50B50 (50% n-heptane and 50% n-butanol, v/v), respectively. Their results showed that as the n-butanol content in blended fuels increased, smaller aggregates and primary particles were produced.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 High-resolution transmission electron microscopy (HRTEM) analysis has been crucial in providing evidence of soot nanostructural disorder. For instance, Verma et al 24 found that, by increasing the oxygen content in the butanol− diesel blends, soot fringe length and fringe separation increased, while the tortuosity decreased. On the contrary, in the study on waste cooking oil methyl ester−diesel blends by Man et al, 25 it was observed that the reduction in soot emission in a DI engine is a result of greater oxidative reactivity due to shorter fringe length and greater tortuosity of diesel engine soot.…”
Section: Introductionmentioning
confidence: 99%